2008
DOI: 10.1038/nature06980
|View full text |Cite
|
Sign up to set email alerts
|

Seismogenic lavas and explosive eruption forecasting

Abstract: Volcanic dome-building episodes commonly exhibit acceleration in both effusive discharge rate and seismicity before explosive eruptions. This should enable the application of material failure forecasting methods to eruption forecasting. To date, such methods have been based exclusively on the seismicity of the country rock. It is clear, however, that the rheology and deformation rate of the lava ultimately dictate eruption style. The highly crystalline lavas involved in these eruptions are pseudoplastic fluids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 27 publications
8
133
0
Order By: Relevance
“…An example of a spatially extended source generating seismicity within a volcanic environment is a volcanic conduit through which magmatic fluids move. In these instances, the generation of low frequency seismicity may be related to the brittle failure of magma itself Lavallée et al 2008;Thomas and Neuberg 2012) or through a stick-slip motion at the conduit edge (Iverson et al 2006). In either case, shallow source depths (1-2 km) and short epicentral distances to seismic receivers (a few kilometers) suggest that a spatially extended source is more realistic than a single point source.…”
Section: The Source Mechanisms Of Low Frequency Earthquakesmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a spatially extended source generating seismicity within a volcanic environment is a volcanic conduit through which magmatic fluids move. In these instances, the generation of low frequency seismicity may be related to the brittle failure of magma itself Lavallée et al 2008;Thomas and Neuberg 2012) or through a stick-slip motion at the conduit edge (Iverson et al 2006). In either case, shallow source depths (1-2 km) and short epicentral distances to seismic receivers (a few kilometers) suggest that a spatially extended source is more realistic than a single point source.…”
Section: The Source Mechanisms Of Low Frequency Earthquakesmentioning
confidence: 99%
“…The trigger mechanism of such seismic energy is further disputed, with suggestions that it may be generated by: (1) a stick-slip motion along the conduit walls as magma ascends (e.g. Iverson et al 2006); (2) the brittle failure of magma itself either through an increase in viscosity and strain rates (Lavallée et al 2008), which may be due to an increase in the ascent rate of magma through the conduit , changes in the crystal and/or bubble concentration in the magma (Goto 1999), or through a change in the geometry of the conduit (Thomas and Neuberg 2012); (3) the interaction between the magmatic and hydrothermal system at depth (e.g. Nakano and Kumagai 2005); or (4) through slow rupture and failure of unconsolidated material on volcanic slopes (Bean et al 2014).…”
Section: Classification By Frequency Contentmentioning
confidence: 99%
“…In particular, when the samples are composite materials as natural magma, the inclusions inevitably cause local fluctuations in the stress and strain rates. For example, Lavallee et al [2008] found that cracking initiates in plagioclase crystals. Specifically, the cracking of solid particles may cause high-frequency fluctuations in the melt which increase brittleness locally.…”
Section: An Explanation For Brittle Fracture In Steady Flowmentioning
confidence: 99%
“…This can happen with a very small fluctuation, when the initial constant stress is close to the critical level. In the experiments by Lavallee et al [2007Lavallee et al [ , 2008, stress fluctuations may be generated by inhomogeneities and may increase b locally.…”
Section: An Explanation For Brittle Fracture In Steady Flowmentioning
confidence: 99%
“…When magma breaks in a laboratory experiment, acoustic emissions-packets of acoustic energy -are released and can be recorded (Benson et al 2008;Lavallee et al 2008). These signals appear to represent large total released amounts of energy when k is short (high _ cÞ, compared to when k is long (low _ cÞ ).…”
Section: Laboratory-scale Unrest Signalsmentioning
confidence: 99%